2021
DOI: 10.2196/20458
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a Multimedia Digital Informed Consent Tool With Traditional Paper-Based Methods: Randomized Controlled Trial

Abstract: Background The traditional informed consent (IC) process rarely emphasizes research participants’ comprehension of medical information, leaving them vulnerable to unknown risks and consequences associated with procedures or studies. Objective This paper explores how we evaluated the feasibility of a digital health tool called Virtual Multimedia Interactive Informed Consent (VIC) for advancing the IC process and compared the results with traditional pape… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 31 publications
2
41
0
Order By: Relevance
“…The positive feedback from the clinical routine is in line with the performance of other systems in the literature. For example, Abujarad et al [ 19 ] reported in a randomized controlled trial that participants had higher satisfaction, higher ability to complete the consent independently, and shorter perceived time to complete the consent process using a different D-IPC system. Hess et al showed that most primary care patients (84%) had no difficulties using a tablet computer-based questionnaire with routine screening content.…”
Section: Discussionmentioning
confidence: 99%
“…The positive feedback from the clinical routine is in line with the performance of other systems in the literature. For example, Abujarad et al [ 19 ] reported in a randomized controlled trial that participants had higher satisfaction, higher ability to complete the consent independently, and shorter perceived time to complete the consent process using a different D-IPC system. Hess et al showed that most primary care patients (84%) had no difficulties using a tablet computer-based questionnaire with routine screening content.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in user comprehension of consent notices were attributed to the overall user satisfaction with and usability of eConsent systems. These systems were described as easy to use, well organized, and more engaging [47,50,53,54,58,[80][81][82][83][84][85][86][87][88][89]. Specifically, a video eConsent system was favored in 7% (1/15) of the studies as participants felt that they could move forward through the video at their own pace, improving their understanding of what they were consenting to [82].…”
Section: User Comprehension Of Consent Notices and Consent Informatio...mentioning
confidence: 99%
“…Improvements in user comprehension of consent notices were attributed to the overall user satisfaction with and usability of eConsent systems. These systems were described as easy to use, well organized, and more engaging [47,50,53,54,58,[80][81][82][83][84][85][86][87][88][89]. Specifically, a video eConsent system was favored in 7% (1/15) of the studies as participants felt that they could move forward through the video at their own pace, improving their understanding of what they were consenting to [82].…”
Section: User Comprehension Of Consent Notices and Consent Informatio...mentioning
confidence: 99%